1988
DOI: 10.1007/bf02556333
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of fetal rat limb bone resorption by phorbol ester (PMA) and ionophore A-23187

Abstract: The present investigation was undertaken to determine if an interaction affecting 45Ca release from prelabeled fetal rat long bones could be elicited by the Ca2+ ionophore, A-23187, and the phorbol ester, 12-myristate 13-acetate (PMA). Treatment with either A-23187 at a concentration of 0.3 microM or PMA at concentrations of 10(-6) M, 10(-7) M, and 10(-8) M produced significant 45Ca mobilization. When A-23187 and PMA were combined, enhanced 45Ca release was observed on days 1 and 2 of culture. The stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…PKC has been implicated in the signalling events associated with numerous cellular responses, including bone resorption. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) The role of PKC in bone remodeling is not clear, however. PKC activity is increased in particulate fractions from parathyroid hormone (PTH)-treated bones or bone cells, (15)(16)(17)(18) and antagonists of PKC prevent PTH-and calcitriol-stimulated resorption.…”
Section: Pkc Isozymes In Osteoblastsmentioning
confidence: 99%
“…PKC has been implicated in the signalling events associated with numerous cellular responses, including bone resorption. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) The role of PKC in bone remodeling is not clear, however. PKC activity is increased in particulate fractions from parathyroid hormone (PTH)-treated bones or bone cells, (15)(16)(17)(18) and antagonists of PKC prevent PTH-and calcitriol-stimulated resorption.…”
Section: Pkc Isozymes In Osteoblastsmentioning
confidence: 99%
“…DAG is a small molecule and it cannot be targeted by traditional genetic knockout approaches. So far pharmacological approaches using the synthetic DAG analog, phorbol ester myristate (PMA), or exogenous DAG species have revealed conflicting results regarding bone resorption and OC formation . Considering that increased DAG levels are observed in conditions associated with bone loss, understanding the direct effects of DAG on the skeleton is mandatory, but it requires an animal model of altered DAG metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…After binding to a single receptor, PTH exerts its biological action via dual signal transduction systems, (13) i.e., the cAMP‐dependent protein kinase A (cAMP/PKA) pathway (14) and the calcium/protein kinase C (Ca 2+ /PKC) pathway (13,15) . Although the pharmacological activation of either pathway can stimulate bone resorption, (16,17) a recent study demonstrated that PTH‐stimulated IL‐6 production is principally mediated by the PKA pathway (5) …”
Section: Introductionmentioning
confidence: 99%